Liminal Participation: Young People's Practices in the Public Sphere Between Exclusion, Claims of Belonging, and Democratic Innovation. Issue 1 (January 2023) - Pitti, Ilaria; Mengilli, Yagmur; Walther, Andreas
Existing understandings of youth participation often imply clear distinctions from non-participation and thus boundaries between "recognized" and "non-recognized" practices of engagement. This article aims at questioning these boundaries. It analyzes young people's practices in the public sphere that are characterized by both recognition as participation and misrecognition or stigmatization as deviant and it is suggested to conceptualize such practices as "liminal participation." The concept of liminality has been developed to describe transitory situations "in-between"—between defined and recognized status positions—and seems helpful for better understanding the blurring boundaries of youth participation. Drawing on qualitative case studies conducted within a European research project, the analysis focuses on how young people whose practices evolve at the margins of the respective societies position themselves with regard to the challenges of liminality and on the potential of this for democratic innovation and change.